Flooding Impairs Fe Uptake and Distribution in Citrus Due to the Strong Down-Regulation of Genes Involved in Strategy I Responses to Fe Deficiency in Roots - Martínez-Cuenca, Mary-Rus; Quinones, Ana; Primo-Millo, Eduardo; Forner-Giner, María A. (2017)
This work determines the ffects of long-term anoxia conditions-21 days-on Strategy I responses to iron (Fe) deficiency in Citrus and its impact on Fe uptake and distribution. The study was carried out in Citrus aurantium L. seedlings grown under flooding conditions (S) and in both the presence (+Fe) and absence of Fe (-Fe) in nutritive solution. The results revealed a strong down-regulation (more than 65%) of genes HA1 and FRO2 coding for enzymes proton-ATPase and Ferric-Chelate Reductase (FC-R), respectively, in -FeS plants when compared with -Fe ones. H+-extrusion and FC-R activity analyses confirmed the genetic results, indicating that flooding stress markedly repressed acidification and reduction responses to Fe deficiency (3.1- and 2.0-fold, respectively). Waterlogging reduced by half Fe concentration in +FeS roots, which led to 30% up-regulation of Fe transporter IRT1, although this effect was unable to improve Fe absorption. Consequently, flooding inhibited 57Fe uptake in +Fe and -Fe seedlings (29.8 and 66.2%, respectively) and 57Fe distribution to aerial part (30.6 and 72.3%, respectively). This evidences that the synergistic action of both enzymes H+-ATPase and FC-R is the preferential regulator of the Fe acquisition system under flooding conditions and, hence, their inactivation implies a limiting factor of citrus in their Fe-deficiency tolerance in waterlogged soils.